Activities of daily living limitations in relation to the presence of pain in community-dwelling older adults - Paweł Balicki; Bartłomiej Konrad Sołtysik; Ewa Borowiak; Tomasz Kostka; Joanna Kostka (Scientific Reports)
Abstract Literature provides data on the relationship between pain and functional limitations in older adults. However, there is a paucity of data on the potential role of pain in activity limitations targeting distinct components of activities of daily living. We investigated functional limitations in all the specific activities of the Activities of Daily Living (ADL) and the Instrumental Activities of Daily Living (IADL) due to the presence of pain in 2992 (1993 women, 999 men) community-dwelling older adults aged 60 to 106 years. 81% of respondents reported pain. For ADL, the most significant associations were observed for bathing/washing, with a 17.9% increase in reported limitations, and for urinary and fecal control, with a 16.1% increase in reported difficulties. For IADL, the most significant relationship between pain and independence was observed for cleaning, shopping and transportation (increase in the frequency of limitations by 14–15%). After adjustments for age and sex, pain contributed to ADL dependence in bathing [OR = 2.41 (1.88–3.08)](odds ratio and corresponding 95% confidence intervals), dressing [OR = 2.05 (1.54–2.73)], toileting [OR = 2.02 (1.47–2.78)], continence [OR = 2.34 (1.81–3.02)], feeding [OR = 2.59 (1.81–3.72)], and transferring [OR = 3.97 (2.58–6.11)]; and to IADL dependence in the ability to use telephone [OR = 1.38 (1.08–1.76)], shopping [OR = 1.92 (1.54–2.39)], food preparation [OR = 1.54 (1.24–1.91)], housekeeping [OR = 1.88 (1.52–2.32)], laundry [OR = 1.51 (1.20–1.90)], transportation [OR = 1.74 (1.40–2.16)], and managing finances [OR = 1.50 (1.18–1.91)]. After adjustments for age, sex, education, BMI, concomitant diseases, depressive symptoms, cognitive function, and nutritional status, pain contributed to dependence in bathing [OR = 1.64 (1.22–2.19)], continence [OR = 1.52 (1.14–2.02)], and transferring [OR = 2.01 (1.23–3.28)]. In the fully adjusted logistic regression model for IADL pain did not contributed to any activities. Our results emphasize that pain occurs in most seniors and is associated with significant limitations in the functioning of older people. A significant association was found between the presence of pain and all dimensions of ADL and IADL. Especially close association was found between pain and dependence in bathing, continence and transferring. Identification of individual limitations in performing activities most affected by pain may help in early detection and prevention of functional limitations among older adults.